Socio-Cultural And Socio-Sexual Factors Influence The Premarital Sexual Behaviour of Javanese Youth In The Era of HIV/AIDS - Zahroh Shaluhiyah (Jurnal Promosi Kesehatan Indonesia, 2007)
Background: In recent years a public health research interest in sexual behaviour of young people has been stimulated by the growing public health concern at the global spread of HIV/AIDS. The research has been continuing to be undertaken for the reason of contributing to epidemiological forecasting of the spread of HIV/AIDS and develop a stronger understanding of sexual behaviour in order to design effective AIDS-related, health education strategies. Although in Indonesia reported that HIV has been transmitted mostly via intra-venous drug users, the greatest long-term public health threat is unprotected sexual intercourse among young people.Method: This paper analyses socio-cultural and socio-sexual dimensions which influence the premarital sexual behaviour of young people. The study was undertaken at aged 18-24 years, university student in urban Central Java with a (500 sample) survey method using structuredand self administered questionnaire.Results: The basic parameter of sexual relationships was found relatively low levels of premarital sexual experience compare with many other countries, but very low level of contraceptive precautions within such activity. The pattern of level of sexual experience was characterised by the level of social activity, level of religiousity, general lifestyle taste andsocio-sexual philosophy. The most important factor influencing the occurrence of premarital sexual intercourse was the factor of socio-sexual philosophy. The respondents which have positive attitudes to premarital sexual intercourse and liberal sexual attitudes tended to have higher levels of premarital sexual intercourse. The key priorities for protecting young people’s sexual health is to continue in maintaining traditional sexual philosophy for the majority of young people and improve “safe sex” for the minority of modern sexual philosophy.Key words: Sexual behaviour, socio-cultural factors, socio-sexual factors, Javanese youth.